Minireview: Transaortic Transcatheter Aortic Valve Implantation: Is There Still an Indication? - Stastny, Lukas; Krapf, Christoph; Dumfarth, Julia; Gasser, Simone; Bauer, Axel; Friedrich, Guy; Metzler, Bernhard; Feuchtner, Gudrun; Mayr, Agnes; Grimm, Michael; Bonaros, Nikolaos (Frontiers in Cardiovascular Medicine, 2022)
Transaortic (TAo) transcatheter aortic valve implantation has become a valid alternative access route in patients with unsuitable femoral arteries. The current literature does not allow to clearly favor one of the alternative access routes. Every approach has its specific advantages. Transaortic (TAo) access is of particular importance in the case of calcifications of the supra-aortic branches and the aortic arch, as under these circumstances other alternative access routes, such as transaxillary or transcarotid, are not feasible. The purpose of this minireview is to give an overview and update on TAo transcatheter aortic valve implantation focusing on indication, technical aspects, and recent clinical data.